2022
DOI: 10.3389/fphar.2022.817213
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Extracts Exert Neuroprotective Effect in Alzheimer’s Disease Mouse Through the Dopaminergic Synapse/Apoptosis Signaling Pathway

Abstract: Background: Alzheimer’s disease (AD) as an age-related, irreversible neurodegenerative disease, characterized by cognitive dysfunction, has become progressively serious with a global rise in life expectancy. As the failure of drug elaboration, considerable research effort has been devoted to developing therapeutic strategies for treating AD. TCM is gaining attention as a potential treatment for AD. Gastrodia elata Blume, Polygala tenuifolia Willd., Cistanche deserticola Ma, Rehmannia lutinosa (Gaertn.)DC., Aco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…[145][146][147] Of note, the underlying mechanism for some compounds with therapeutic potential in AD is apoptosis inhibition. 148,149 As mentioned before, several studies have shown cholesterol efflux is impaired in AD patients. Therefore, CSF CEC impairment results in lower cholesterol supply to neurons and promotes apoptosis and neurodegeneration.…”
Section: Discussionmentioning
confidence: 86%
“…[145][146][147] Of note, the underlying mechanism for some compounds with therapeutic potential in AD is apoptosis inhibition. 148,149 As mentioned before, several studies have shown cholesterol efflux is impaired in AD patients. Therefore, CSF CEC impairment results in lower cholesterol supply to neurons and promotes apoptosis and neurodegeneration.…”
Section: Discussionmentioning
confidence: 86%
“…It is synthesized by choline acetyltransferase, AchE, an enzyme found in cerebrospinal fluid and plasma. The AchE is an enzyme that metabolizes Ach at synaptic clefts ( Karami et al, 2021 ; Huang et al, 2022 ). To further test neuroprotective effects of IMP on brain damage, we examined cholinergic dysfunction, as indicated by a decreased Ach content (5.5 fold).…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation of MAPKs is essential for regulating cell division, proliferation, and differentiation. Ruther more, MAPKs can trigger apoptosis ( Kahkhaie et al, 2019 ; Yu et al, 2019 ; Ijomone et al, 2021 ; Huang et al, 2022 ). Moreover, as shown above, IMP suppressed the activation of p38 and JNK caused by AlCl3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This preparation has been shown to reduce depression-like behavior via the production of monoamines in a UCMS rat model [ 91 ] and the expression of glial fibrillary acidic protein (GFAP) and BDNF in the hippocampus [ 92 ]. In addition, other studies have reported that the Qisheng Wan formula [ 93 ]; Bushen Tiansui decoction [ 94 ]; GPCRAC with extracts from Polygala tenuifolia , Rehmannia lutinosa , Gastrodia elata , Cistanche deserticola , AG, and Curcuma longa [ 95 ]; Bazhu decoction [ 96 ]; and Chong Myung Tang [ 97 ] ameliorated the cognitive impairment of AD animals. Moreover, a study reported that the Yishen Huazhuo decoction improved brain activity in AD patients [ 98 ].…”
Section: Resultsmentioning
confidence: 99%